Diagnóstico de Brucelose, Tuberculose, Anemia Infecciosa Equina e Mormo. - Batista, Givanildo Teixeira (Universidade Federal do Tocantins, 2023)
The supervised training course was carried out between 02 October and 04 December 2017, in the area of Animal Health, in the city of Araguaína - Tocantins - under the guidance of Veterinarian José Wilson Dias Brito, with a workload of 380 hours. The stage involved in all stages of blood collection, centrifugation, accommodation, shipping (Mormo and Equine Infectious Anemia- AIE), analysis of the serum for brucellosis and, also, the reading for tuberculosis. At the moment, I was able to know how to do all the procedures for collecting and sending the materials, always considering the animal welfare, all this learning made me realize how important is the accomplishments of the periodic examinations of the production animals using the norms and techniques for achieving them, with a focus on public health.